NZ 2018
DOI: 10.20417/nzjecol.42.11
|View full text |Cite
|
Sign up to set email alerts
|

The secret service – analysis of the available knowledge on moths as pollinators in New Zealand

Abstract: Abstract:On a global-scale, moths (Lepidoptera) are considered to be important pollinators for many plant families. However, the assumption that moths are also involved in pollination in New Zealand is underpinned by relatively little research. Here we review the evidence for moth pollination of flowering plants in New Zealand and compare the quality of evidence available with that of the global literature. Globally, the majority of experimental studies have focused on the hawkmoths (Sphingidae) and other spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 39 publications
(69 reference statements)
1
19
0
2
Order By: Relevance
“…Proportion of moths carrying pollen Average number of pollen grains carried Total number of pollen grains carried in D. longifolium shrubland despite fewer moths being caught there than in other zones. The floral characteristics of D. longifolium align with what is known as the moth pollination syndrome, which involves plants having pale, tubular flowers offering nectar rewards and that are strongly scented at night ( Proctor et al 1996;Buxton et al 2018). The inflorescence of D. longifolium is a 6-to 15-flowered raceme 4-5 cm long.…”
Section: Exposure Gradientmentioning
confidence: 93%
See 3 more Smart Citations
“…Proportion of moths carrying pollen Average number of pollen grains carried Total number of pollen grains carried in D. longifolium shrubland despite fewer moths being caught there than in other zones. The floral characteristics of D. longifolium align with what is known as the moth pollination syndrome, which involves plants having pale, tubular flowers offering nectar rewards and that are strongly scented at night ( Proctor et al 1996;Buxton et al 2018). The inflorescence of D. longifolium is a 6-to 15-flowered raceme 4-5 cm long.…”
Section: Exposure Gradientmentioning
confidence: 93%
“…A pollinator's importance is dependent not only on its efficiency in transferring a large amount of pollen but also on the abundance and visiting rate of the pollinator (Herrara 1987;Newstrom & Robertson 2005). Pollinator efficiency can be measured and inferred in many ways; this study used the average number of pollen grains as well as the proportion of moths found to carry pollen as a proxy for quality of pollination service (see Buxton et al [2018] and MacGregor et al [2014] for reviews of the way pollination via moths is measured globally). Both approaches used in this study indicate that the potential role of moths as pollinators may be most important in the intermediate shrubland zone and least important in the sheltered rātā forest.…”
Section: Exposure Gradientmentioning
confidence: 99%
See 2 more Smart Citations
“…There are reviews of general insect pollination (e.g., Kevan & Baker 1983), but only recently have any focused on moths (Macgregor et al, 2015;Hahn & Brühl, 2016;Buxton et al, 2018), thus beginning to coalesce the extensive, yet diffuse literature. These reviews signal a maturation of moth-pollination ecology, which is long overdue, as studies of moth pollination have consistently lagged behind those of the conspicuous diurnal pollinators, such as bees and butterflies (Johnson & Steiner 2000, Klein et al 2007).…”
Section: Introductionmentioning
confidence: 99%